Kedaulatan Rakyat dalam Pemilihan Kepala Daerah Asimetris: Studi Konstitusional terhadap Daerah Khusus, Daerah Istimewa, dan Otorita IKN - Luh Putu Vera Astri Pujayanti; Muhammad Suhardi (IPDN Kampus NTB, 2025)
This study aims to analyze the construction of popular sovereignty in asymmetric regional head selection and to compare local democracy models in the Special Region of Yogyakarta, Special Region of Jakarta, Aceh, Papua, and the Nusantara Capital Authority. This research uses a qualitative method with normative juridical research. The approaches applied include statutory, conceptual, comparative, and normative case approaches. The data consist of primary, secondary, and tertiary legal materials collected through library research. The analysis is conducted qualitatively and prescriptively through legal interpretation and legal reasoning. The findings show that popular sovereignty in asymmetric local government is not always expressed through direct elections. Yogyakarta represents a historical-cultural privilege model through the appointment of the governor and vice governor. Jakarta maintains direct elections at the provincial level but limits direct elections at the city and regency administrative levels. Aceh reflects a special autonomy model based on political reconciliation and local political parties. Papua demonstrates a special autonomy model based on the cultural representation of Indigenous Papuans. The Nusantara Capital Authority represents the most problematic model because its head is appointed by the President. This study proposes constitutional parameters for assessing asymmetric local democracy, namely constitutional legitimacy, meaningful public participation, citizen representation, accountability of local government leaders, and protection of the substance of local democracy. The findings affirm that regional asymmetry may be constitutionally justified as long as it does not eliminate public control over local governance.